Collisional Excitation of Fluorine Like Tungsten using Relativistic Dirac Atomic R-matrix Method (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
We report the new extensive calculations for collision strengths and effective collision strengths of Electron impact excitation of fine structure transitions in F-like W using fully relativistic Dirac Atomic R-matrix Code. We have included all 113 target states which belong to 2s22p5, 2s2p6, 2s22p43l, 2s2p53l, 2p63l configurations. The convergence of reported collision strengths is tested by performingthe same calculations for lesser number of target states which verify the individuality of our results.Effective collision strengthsover a wide temperature range 104-107K are computed. Further, to assess the accuracy and authenticity of our target states energies, a similar parallel calculation has also been performed using a fully relativistic distorted wave (RDW) method and a comparison of energy levels with NIST, FAC and other experimental observations has been made. We believe that the collision strength results for all forbidden transitions within the 113 fine structure levels, presented in this paper will play a substantial role in fusion plasma diagnostics.
Keywords: Energy levels; Collision strength; Excitation